On the Relative Effectiveness of Stochastic Dominance Rules: Extension to Decreasingly Risk-Averse Utility Functions - Vickson, R. G.; Altmann, M. (Journal of Financial and Quantitative Analysis, 1977)
R. G. Vickson, M. Altmann, On the Relative Effectiveness of Stochastic Dominance Rules: Extension to Decreasingly Risk-Averse Utility Functions, The Journal of Financial and Quantitative Analysis, Vol. 12, No. 1 (Mar., 1977), pp. 73-84